Novel dystrophin mutations revealed by analysis of dystrophin mRNA: alternative splicing suppresses the phenotypic effect of a nonsense mutation - Fajkusová, L; Lukás, Z; Tvrdíková, M; Kuhrová, V; Hájek, J; Fajkus, J (Neuromuscular disorders, 2001)
The complete dystrophin mRNA sequence has been analyzed in 20 Duchenne muscular dystrophy and Becker muscular dystrophy patients. In 13 cases, deletions in mRNA were detected using reverse transcription-polymerase chain reaction and in another seven cases, point mutations were found using the protein truncation test. Sixteen patients diagnosed with Duchenne muscular dystrophy showed the presence of deletions or of nonsense point mutations. From four patients with the Becker muscular dystrophy phenotype, three cases were associated with deletions conserving the translational frame and one was associated with a nonsense mutation E1110X. In the case of the E1110X mutation, an alternative splicing of dystrophin mRNA (3485-3640del) was detected in this patient which included the E1110X mutation site (nucleotide 3536) and did not change the translation reading frame. Individual nonsense point mutations were characterized by sequence analysis, which showed five novel mutations with respect to those reported in the Cardiff Human Gene Mutation Database http://uwcm.web.cf.ac.uk/uwcm/mg/hgmd0.html and the Leiden muscular dystrophy pages http://www.dmd.nl/.
Keywords: dospělí; kosterní svaly; Phenotype; dítě; předškolní dítě; Adult; Codon, Nonsense; mutační analýza DNA; svalové dystrofie; Adolescent; Immunohistochemistry; Muscular Dystrophies; lidé; DNA Mutational Analysis; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; Muscle, Skeletal; imunohistochemie; nesmyslný kodon; RNA, Messenger; Point Mutation; Reverse Transcriptase Polymerase Chain Reaction; Child, Preschool; dystrofin; bodová mutace; Dystrophin; alternativní sestřih; Child; fenotyp; Alternative Splicing; mladiství; Humans